2nd International RILEM Symposium on Advances in Concrete Through Science and Engineering 2006
DOI: 10.1617/2351580028.078
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of autogenous shrinkage of concrete based on paste measurements

Abstract: In order to be able to improve concrete modelling based on its constituent, more knowledge is needed about the material behaviour of these constituents. In this research the focus is on the behaviour of hardening concrete, therefore the properties of hardening cement are of most relevance. Information about cement paste behaviour can be used as input for computer models that are able to represent concrete as a heterogeneous material. During the development of these models the output has to be verified with dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The paste deformations were measured with a newly developed mini-TSTM apparatus and compared with the full-scale TSTM results. Numerical simulations with the Lattice model [2] also show the contribution of autogenous shrinkage in the early age stress development. In this paper an attempt is made to measure the deformations for both cement paste and concrete and to examine the differences by means of numerical simulations.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…The paste deformations were measured with a newly developed mini-TSTM apparatus and compared with the full-scale TSTM results. Numerical simulations with the Lattice model [2] also show the contribution of autogenous shrinkage in the early age stress development. In this paper an attempt is made to measure the deformations for both cement paste and concrete and to examine the differences by means of numerical simulations.…”
Section: Introductionmentioning
confidence: 92%
“…With a Lattice model [2] the deformations measured from the cement paste ( Figure 5) are taken as input to simulate the behaviour of concrete. The measured shrinkage of a cement paste with CEMIII/B (580 m 2 /kg) is used with a w/c ratio of 0.44.…”
Section: Simulations Of Autogenous Shrinkagementioning
confidence: 99%
See 2 more Smart Citations
“…Recent numerical simulations, using the lattice model for predicting stress development from a mini temperature stress testing machine (TSTM) on small paste specimens, where thermal effects from heat of hydration are minimal, concluded that a poor agreement was obtained between predicted stresses by using three different models for obtaining stress relaxation modulus (Schlangen et al 2006). The first model was based on an assumption of instant relaxation that internal stresses will cause instant deformation of the micro-porous hydration products.…”
Section: Introductionmentioning
confidence: 99%